Current Patterns on East Season in The Northern Waters of The Sunda Strait - Ridho Tondang; Kunarso Kunarso; Jarot Marwoto; Heryoso Setiyono; Hariyadi Hariyadi (Indonesian Journal of Oceanography, 2020)
The northern waters of Sunda Strait is the first Indonesian Archipelagic Sea Lanes. (ALKI I) which is an important and a very crowded shipping lane. The first Indonesias Archipelagic Sea Lanes (ALKI 1) connects the marine traffic from Africa, West Australia to South China Sea, Japan and the other way around. Indonesia in determining the archipelagic sea lanes considers several criterias, one of them is the oceanographic condition which is the ocean currents. The purpose of this research is to examine the characteristic of the ocean current pattern in the northern waters of Sunda Strait. The stages of this research include the measurement of field data, field data processing, and hydrodynamics modeling. The research location was determined by purposive sampling method. The determination of the research location follows the path of bathymethry. The result of field measurement is processed then used as data validation of current simulation result of hydrodinamic model. The result of the hydrodynamics model simulation showing the direction of current in northern waters of Sunda Strait moving back and forth following the tidal periods. The direction of the dominant current in northern waters of Sunda Strait is to Northeast (flood current) and Southwest (ebb current). The current velocity in northern waters of Sunda Strait is approximately between 0,0122 m/s and 2,590 m/s. The maximum velocity of the current belongs to several observation points that located in the seabed. This is to be expected due to the impact of Indonesia Through Flow.